AKSI RAMAH PEDULI MANGROVE DALAM RANGKA MEMPERINGATI HARI HUTAN SEDUNIA - Nina Mistriani; Aletta Dewi Maria Th; Moch. Rizqy Eko Saputra; Bethary Henandriati K1; Nindy Fatma Rizkyka; Sabrina Diva Pramesti (Jurnal Pengabdian Masyarakat Waradin, 2021)
The mangrove forest ecosystem is an important habitat for forest conservation, so one area that has the potential for developing mangrove ecotourism in the city of Semarang is the tourist village of Tapak Tugurejo, Tugu district. Mangrove forest is a mangrove forest in brackish swamp land, usually influenced by tides, generally found on the coast / bay forest that is protected from big waves with biodiversity. Therefore, the importance of direct activities to raise awareness to the community about the importance of planting mangroves can prevent abrasion, especially in the tourist village of Tapak Tugurejo. This activity is carried out by the TVO (Tourism Volunteer Organization) organization. In general, the activities were followed enthusiastically by other participants. The research method uses qualitative methods, and the type of case study research. The results of this service are expected to understand and take great benefits for youth and the community to care for the environment, as well as useful for preventing abrasion in the tourist village of Tapak Tugurejo